Solar chimney for enhancing thermal comfort in individual housing in a semi-humid climate - Louafi, Samira (Technium Social Sciences Journal, 2022)
Nowadays, the rational use of energy resources is placed at the center of our concerns. The use of renewable energy sources such as solar energy, wind, and geothermal energy are very interesting alternatives to meet our needs for comfort inside our homes. In semi-humid climates, natural ventilation is recommended to improve thermal comfort. In this way, natural ventilation using renewable energy without the need for mechanical equipment has gained in importance. A solar chimney is one of this technology that can be used to improve the ventilation of a residential or commercial building and uses the same principle at a chimney. In this study, the effect of the presence of a solar chimney on hygrothermal comfort was evaluated. A simulation will be carried out by EDSL TAS software; to evaluate and compare the effect of natural ventilation on hygrothermal comfort in the winter period of the individual dwelling. Four scenarios are selected; without ventilation, with cross ventilation, and by the integration of the solar chimney. Also varied shapes of canals. The results show that a solar chimney based on the thermal chimney effect can improve natural ventilation.